Análise das causas técnicas e gerenciais da paralisação de obras públicas no Brasil e no Amapá: estudo comparativo das obras em comum entre o Obras.gov.br e as auditorias do Tribunal de Contas da União (2021–2024) - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2026)
This Final Graduation Project aims to analyze the panorama of public works that remain unfinished or paralyzed in the State of Amapá, identifying their causes and socio-economic impacts, in light of the Fiscobras 2024 Report from the Federal Court of Accounts of Brazil (TCU) and data from the Obras.gov.br Portal. The research is applied, with a qualitative and quantitative mixed-method approach, and is characterized as descriptive and exploratory. Data were collected from 1,113 works registered in the 16 municipalities of Amapá, of which 33 were paralyzed, unfinished, suspended, or canceled, representing approximately R$ 144 million in planned investments. The methodology involved cross-referencing and reclassification of databases from federal and municipal sources, using statistical and textual correspondence techniques (fuzzy matching), complemented by official and news based verification. The results showed that the Transport Infrastructure sector accounts for 42% of the paralyzed works and more than half of the total value, followed by Sanitation, Education, and Health. The main causes are related to discontinuity of financial transfers (45%), technical planning failures (30%), contractual issues (15%), and institutional barriers (10%). The analysis also revealed a low level of convergence (26%) between the TCU and Obras.gov.br databases, reflecting the lack of standardization and integration among public works monitoring systems. It is concluded that the paralysis of public works in Amapá reflects, on a regional scale, the structural weaknesses of Brazilian public governance, marked by insufficient planning, administrative discontinuity, and lack of interoperability across federative systems. The study recommends the implementation of a national unified public works identifier, the strengthening of local management units, the adoption of multiannual binding planning mechanisms, and the enhancement of transparency and social accountability. These measures are essential to reduce the number of paralyzed works and to promote efficiency, integrity, and effectiveness in public infrastructure management.
Keywords: Transparência Governamental; Gestão Pública; Transparência Governamental; CNPQ::ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL; ODS 11 – Cidades e comunidades sustentáveis; ODS 16 – Paz, justiça e instituições eficazes; ODS 9 – Indústria, inovação e infraestrutura